Health perception and restorative experience in the therapeutic landscape of urban wetland parks during the COVID-19 pandemic - Jiang Li; Yating Chang; Xiaoxi Cai; Shaobo Liu; You Peng; Tao Feng; Jialing Qi; Yifeng Ji; Yiting Xia; Wenbo Lai (Frontiers Media S.A., 2023)
IntroductionThe effects of restoration and inspiration in the therapeutic landscape of natural environments on visitors during the COVID-19 pandemic have been well-documented. However, less attention has been paid to the heterogeneity of visitor perceptions of health and the potential impacts of experiences in wetland parks with green and blue spaces on visitors' overall perceived health. In this study, we investigate the impact of the restorative landscapes of wetland parks on visitors' health perceptions in the context of the COVID-19 pandemic.MethodsIn our survey, 582 respondents participated in an online questionnaire. We analyzed the respondents' health perceptions in terms of latent class analysis, used multinomial logistic regression to determine the factors influencing the potential categorization of health perceptions, and used structural equation modeling to validate the relationships between health perceptions of different groups and landscape perceptions of wetland parks, restorative experiences, and personality optimistic tendencies.ResultsThe results identified three latent classes of health perceptions. Gender, marital status, education, occupation, income, distance, frequency of activities, and intensity of activities were significant predictors of potential classes of perceived health impacts among wetland park visitors.DiscussionThis study revealed the nature and strength of the relationships between health perception and landscape perception, restorative experience, and dispositional optimism tendencies in wetland parks. These findings can be targeted not only to improve visitor health recovery but also to provide effective references and recommendations for wetland park design, planning, and management practices during and after an epidemic.